Can biological maturity status influence the selection of the field position in young soccer players? - Horta, L.; Miller, R.; Rio, C.; Miranda, M.; Soares Branco, P.; Rodrigues, J.; Aguiar, P.; Costa, O. (1999)
Soccer is a sport that involves not only resistance tasks but also explosive ones, like jumping or sprinting. The biological maturity status in adolescents can influence their performance level in those tasks. In a theoretical basis, the selection of field positions in young soccer players can be influenced by their biological maturity status because those field positions require different skills in terms of resistance and explosive tasks. We studied a total of 145 young soccer players with a distribution of chronological ages between 11 and 19 years, that played Soccer for at least two years and trained at least four hours weekly. In each player we studied the chronological age, field position (goalkeepers n = 15; lateral backs - n = 23; central backs - n = 25; mid-fields - n = 57; forwards - n = 25) and skeletal maturity (Greulich-Pyle Method). Skeletal and chronological ages were contrasted as SA-CA. The players were also classified as late, average and early maturing on the basis of SA-CA differences, with the average category including boys with SA within + 1.0 year of CA. Mean SA was in advance of mean CA in all field positions (goalkeepers - 15,3 + 2.4 and 14,6 + 1.8 years; lateral backs - 15,2 + 2.1 and 14,9 + 1.7 years; central backs - 16,3 + 1.7 and 15,3 + 1.5 years; mid-fields - 15,0 + 2.6 and 14,9 + 1.8 years; forwards - 15,4 + 2.2 and 14,7 + 1.8 years), but the differences were statistically significant only in goalkeepers, central backs and forwards. Eighteen boys were already skeletally mature and were not included for the purpose of calculating SA-CA differences. The proportion of late maturing boys decreased with increasing age in all the field positions. The percentages of early and late maturing boys were, respectively, goalkeepers - 53,3% - 6,7%; lateral backs - 30,4% - 13,0%; central backs - 68,0% - 0%; mid-fields - 31,6% - 19,3%; forwards - 40,0% - 8,0%. The results of this comparative analysis suggest that Soccer systematically excludes late maturing boys and favours average and early maturing boys, specially to play as goalkeepers, central backs and forwards. It is also possible that late maturing boys are mainly selected to play in lateral back and mid-field positions but they gradually drop-out as age and sport specialisation increase.